2007
DOI: 10.1002/ppul.20585
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexamethasone injection for acute bronchiolitis in hospitalized children: A randomized, double‐blind, placebo‐controlled trial

Abstract: Controversy over the efficacy of systemic corticosteroids for acute bronchiolitis initiated this study. We conducted a randomized, double-blind, placebo-controlled trial to examine the efficacy of single dexamethasone injection for the treatment of acute bronchiolitis in young hospitalized children. The study, performed at the pediatric wards of a University Hospital and its affiliated hospital in Thailand, included 174 previously healthy children under 2 years of age, hospitalized with acute bronchiolitis. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…4 Many commonly used therapies such as bronchodilators and corticosteroids have no proven efficacy in the treatment of bronchiolitis. [5][6][7][8][9][10][11][12][13][14][15][16][17] The We considered several additional covariates in our analysis. The NHAMCS collects age in days for patients under 1 year of age, and age in years only for those aged .1 year.…”
Section: Discussionmentioning
confidence: 99%
“…4 Many commonly used therapies such as bronchodilators and corticosteroids have no proven efficacy in the treatment of bronchiolitis. [5][6][7][8][9][10][11][12][13][14][15][16][17] The We considered several additional covariates in our analysis. The NHAMCS collects age in days for patients under 1 year of age, and age in years only for those aged .1 year.…”
Section: Discussionmentioning
confidence: 99%
“…13 14 The Cochrane review showed no evidence of benefit for systemic steroids. 15 One trial found that a single injection of dexamethasone may help in acute bronchiolitis, 16 Cyanosis or really severe respiratory distress (respiratory rate >70 breaths/min, nasal flaring and/or grunting, severe chest wall recession) Marked lethargy leading to poor feeding Respiratory distress preventing feeding (<50% of usual intake in past 24 hours) Apnoeic episodes Diagnostic uncertainty (toxic infant, temperature ≥40 degrees centigrade) …”
Section: Are Investigations Necessary?mentioning
confidence: 99%
“…One trial (n=174) showed that a single dose of intravenous dexamethasone (0.6 mg/kg) results in (statistically but not clinically significant) shorter duration of hospitalization and time for resolution of respiratory distress [15,16].…”
Section: Steroids (Oral/inhaled)mentioning
confidence: 99%